Islamic Economic Ethics in the Formulation of Export Import Policy in the Modern Era - Mut Mainah; Surya Sukti (Universitas Trunojoyo Madura, 2025)
The era of economic globalization is growing, so that the application of Islamic ethics in import activities in Indonesia is becoming increasingly relevant to the global demand for sustainable and ethical business practices. This research aims to examine how Islamic ethics can be applied practically in import activities, as well as its impact on the economy and people's welfare. The method used in this study is qualitative with a literature study to evaluate the extent to which import policies can reflect Islamic values. The results of the study show that Islamic ethics not only regulates aspects of economic transactions but also morality in business, prohibits the import and import of goods that have haram elements, the practice of usury, and fraud, and emphasizes the balance between economic benefits and environmental sustainability and community welfare. Sharia-based import policies aim to support local economies, pay attention to social and environmental impacts, and ensure transparency and fairness. With the integration of Islamic values into global trade regulations, import policies can be instrumental in creating a fairer, more sustainable, and beneficial economic system for the wider community.